Biohydrogels for medical applications: A short review - OKTAR, FAİK NÜZHET; EROĞLU, MEHMET SAYIP; GÜNDÜZ, OĞUZHAN (ACG PUBLICATIONS, 2018)
Hydrogels have been widely used as drug delivery systems for scaffold production (in different soft and hard tissue engineering, including bones), thanks to their biocompatibility and biodegradability. In addition to the possibility of synthesizing a wide range of hydrogels from various natural and synthetic polymers, they are suitable for scaffold production. Moreover, they can have antimicrobial, antitumor and analgesic functions due to their intrinsic properties or through addition of proper biologically active agents. In this article, different types of hydrogels are reviewed alongside their application areas. Different methods are applied for the preparation of hydrogels and their compositions, and are strongly correlated with the morphological and mechanical properties of the synthesized hydrogels, which had a great influence on the performances of the respective scaffolds. The most effective ways to produce the desired scaffolds are mold casting, especially, 3D printing and electrospinning due to the ability to manipulate and control the shape and size of the desired scaffold as well as their microstructure.
Keywords: processing routes; chemical composition versus medical applications; hydrogels; SULFATE-BASED HYDROGEL; DRUG-DELIVERY; ELECTROHYDRODYNAMIC ATOMIZATION; ELECTROSPUN SCAFFOLDS; CONTROLLED-RELEASE; NETWORK STRUCTURE; BLOCK-COPOLYMER; LOCAL-DELIVERY; CROSS-LINKING; HIGH-STRENGTH